Northern Ireland life and times survey, 2023 - Devine, Paula (Northern Ireland Life and Times Survey, 2024)
From 1998 to 2000, NILT surveys were undertaken as a face-to-face interview, followed by a short self-completion questionnaire. However, due to the COVID-19 pandemic, the survey has since been undertaken online. Respondents could also request to complete the survey via a phone interview if they desired.